Early Nutrition and Risk of Type 1 Diabetes: The Role of Gut Microbiota - Verduci, Elvira; Mameli, Chiara; Amatruda, Matilde; Petitti, Agnese; Vizzuso, Sara; El Assadi, Farah; Zuccotti, Gianvincenzo; Alabduljabbar, Shaikha; Terranegra, Annalisa (Frontiers in Nutrition, 2020)
Type 1 diabetes (T1D) appears most frequently in childhood, with an alarming increasing incidence in the last decades. Although the genetic predisposition is a major risk factor, it cannot solely explain the complex etiology of T1D which is still not fully understood. In this paper, we reviewed the most recent findings on the role of early nutrition and the involvement of the gut microbiota in the etiopathogenesis of T1D. The main conclusions that are withdrawn from the current literature regarding alleviating the risk of developing T1D through nutrition are the encouragement of exclusive breast-feeding during the first 6 months of life and the avoidance of early complementary foods and gluten introduction (before 4 months of age) as well as cow milk introduction before 12 months of life. These detrimental feeding habits create a gut microbiota dysbiotic state that can contribute to the onset of T1D in infancy. Finally, we discussed the possibility to introduce probiotics, prebiotics and postbiotics in the prevention of T1D.